2013
DOI: 10.3168/jds.2012-5865
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Shiga toxin-producing and generic Escherichia coli during production and ripening of semihard raw milk cheese

Abstract: 21The fate of five different E. coli strains, including three Shiga-toxin producing E. coli (STEC) 22 strains, was analyzed during the production and ripening of semi-hard raw milk cheese. The 23 strains, that were previously isolated from raw milk cheese, were spiked into raw milk prior to 24 cheese production at two different levels (about 10 1 CFU/ml and 10 3 CFU/ml, respectively). 25Two cheese types were produced, that differed in cooking temperatures (40 and 46°C). The 26 cheeses were sampled during ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 16 publications
1
32
0
6
Order By: Relevance
“…This could suggest that the LHR does not provide significant general benefits to E. coli , or that transfer of LHR only rarely occurs in this organism. On the other hand, previous studies have investigated E. coli strains isolated from raw milk cheeses in Switzerland and shown that many of them exhibit increased heat resistance in milk at subpasteurization temperatures and during cheese ripening (Peng et al, 2012, 2013a,b). We recently screened a total of 256 of these E. coli raw milk cheese isolates for heat resistance markers clpK and an additional LHR marker gene, demonstrating that 93 (36.3%) of them were positive for both (while 24 and 9 isolates, respectively, were positive for one marker).…”
Section: Introductionmentioning
confidence: 99%
“…This could suggest that the LHR does not provide significant general benefits to E. coli , or that transfer of LHR only rarely occurs in this organism. On the other hand, previous studies have investigated E. coli strains isolated from raw milk cheeses in Switzerland and shown that many of them exhibit increased heat resistance in milk at subpasteurization temperatures and during cheese ripening (Peng et al, 2012, 2013a,b). We recently screened a total of 256 of these E. coli raw milk cheese isolates for heat resistance markers clpK and an additional LHR marker gene, demonstrating that 93 (36.3%) of them were positive for both (while 24 and 9 isolates, respectively, were positive for one marker).…”
Section: Introductionmentioning
confidence: 99%
“…Increase of 3.5 log cfu g À1 at day 1 (concentration effect and growth); slow and continuous decrease during ripening; generic E. coli Survived at higher counts; 6 cheeses with low inoculum: >1 log cfu g À1 at end of ripening; after enrichment: VTEC detection in almost all cheeses Peng et al (2013) Inoculation of 2.4 log cfu mL À1 S. aureus in milk; 3.3 log cfu mL…”
Section: Identification Of Main Microbiological Hazards In Dairy Prodmentioning
confidence: 99%
“…coli raw milk isolates (15). These strains were further analyzed, and the results confirmed increased resistance to subpasteurization temperatures in milk (16) as well as boosted survival during ripening of semihard raw milk cheese (17). In a recent study, 256 E.…”
Section: Introductionmentioning
confidence: 85%